The Influence of Brittleness of Interlayers on the Failure Behavior of Bedding Rock; Experimental Test and Particle Flow Code Simulation - Mortezaei, Rahim; Mohammadi, Seyed Davoud; Sarfarazi, Vahab; Bahrami, Reza (Periodica Polytechnica Civil Engineering, 2024)
In the present study, the effects of angle and brittleness of interlayers on the shear failure behavior of notched bedding rock have been scrutinized using experimental shear tests and particle flow code (PFC) simulation. Notched bedding models with dimensions of 20 cm × 24 cm × 5 cm containing soft interlayer and hard interlayer were prepared. The ratio of compressive strength to tensile strength in soft gypsum and hard gypsum are 12 and 7.8, respectively. The layer angel changed from 0° to 90° with an increment of 15°. The lengths of notches in each model are similar and were equal to 20 mm, 40 mm, and 60 mm. Models were tested by Punch shear by displacement loading rates of 0.05 mm/min. Results showed that pure tensile fracture was developed from the tip of the notch, and propagated in the direction of the shear loading axis till coalescence with the model boundary. Whereas soft brittle gypsum has less deformability in comparison to hard ductile gypsum therefore the continuity of shear displacement associated with crack growth in soft interlayer was less than that in hard interlayer. Also, soft brittle gypsum has less shear strength in comparison to hard ductile gypsum therefore the shear strength of bedding rock has maximum value when hard ductile gypsum was occupied more percentage of shear surfaces. The failure mechanism was alike in both the numerical simulation and the experimental test.